2014
DOI: 10.3109/07388551.2014.922915
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus atrophaeus:main characteristics and biotechnological applications – a review

Abstract: The genus Bacillus includes a great diversity of industrially important strains, including Bacillus atrophaeus (formerly Bacillus subtilis var. niger). This spore-forming bacterium has been established as industrial bacteria in the production of biological indicators for sterilization, in studies of biodefense and astrobiology methods as well as disinfection agents, in treatment evaluation and as potential adjuvants or vehicles for vaccines, among other applications. This review covers an overview of the funda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 95 publications
1
46
0
Order By: Relevance
“…While we were unable to find any study in the literature specifically comparing the resistance of B. anthracis Ames to B. atrophaeus (aka B. subtilis var Niger) upon exposure to HPV, B. atrophaeus is phenotypically similar to B. subtilis except for the production of pigment (Sella et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…While we were unable to find any study in the literature specifically comparing the resistance of B. anthracis Ames to B. atrophaeus (aka B. subtilis var Niger) upon exposure to HPV, B. atrophaeus is phenotypically similar to B. subtilis except for the production of pigment (Sella et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…B. atrophaeus has a wide variety of biotechnological applications. Sella et al [30] studied the taxonomy, multicellularity, life cycle, and some aspects of biotechnological applications of Bacillus atrophaeus as a biomolecule producer. They showed that Bacillus atrophaeus could be a vehicle and adjuvant for vaccine and as a biological indicators to evaluate the efficiency of the sterilization processes.…”
Section: Bacterial Identificationmentioning
confidence: 99%
“…Cardboard packaging materials with synthetic surfaces are often sterilized by a combination of hydrogen peroxide (H 2 O 2 ) and mild thermal inactivation (Toledo 1988). For H 2 O 2 -based inactivation, spores of Bacillus subtilis and Bacillus atrophaeus are used as biological indicators (BI) to validate the inactivation effect (VDMA 2006;Sella et al 2014). To achieve short inactivation times allowing fast filling processes, vaporized H 2 O 2 at high concentrations is applied.…”
Section: Introductionmentioning
confidence: 99%